2006
DOI: 10.1063/1.2213966
|View full text |Cite
|
Sign up to set email alerts
|

Single silicon vacancy-oxygen complex defect and variable retention time phenomenon in dynamic random access memories

Abstract: The variable retention time phenomenon has recently been highlighted as an important issue in dynamic random access memory (DRAM) technology. Based on electrically detected magnetic resonance and simulation studies, we suggest that a single Si vacancy-oxygen complex defect is responsible for this phenomenon, when the defect is embedded in the near surface drain-gate boundary of a DRAM cell.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 10 publications
1
13
1
Order By: Relevance
“…On average, the effect of RTN seems equivalent to a V th shift of about 0.02V to 0.06V, which tallies with measured data [4]. 6 Fig . 16 quantifies the bit-error impact of RTN on SRAM arrays.…”
Section: B Statistical Inferences About Rtn-induced Sram Failuressupporting
confidence: 85%
See 2 more Smart Citations
“…On average, the effect of RTN seems equivalent to a V th shift of about 0.02V to 0.06V, which tallies with measured data [4]. 6 Fig . 16 quantifies the bit-error impact of RTN on SRAM arrays.…”
Section: B Statistical Inferences About Rtn-induced Sram Failuressupporting
confidence: 85%
“…16 quantifies the bit-error impact of RTN on SRAM arrays. Using a normal distribution for V th and the trap profiling model of [2], we have computed the probability of write failure as V dd is increased from 0.7 V to 1.0 V. As 6 Please note that N in Fig. 15 is the total number of device traps, not the number of active traps.…”
Section: B Statistical Inferences About Rtn-induced Sram Failuresmentioning
confidence: 99%
See 1 more Smart Citation
“…RTN in Dynamic Random Access Memories (DRAM) has already been reported in the late eighties (35,36), giving rise to the so-called variable retention time phenomenon. In this case, the trapping is associated with p-n junction leakage current and with traps in the silicon depletion region (37,38). Recent results have demonstrated that the RTN issue will become even more pronounced for future Resistive RAM (ReRAM) (39)(40)(41)(42) or Phase-Change Memories (43)(44)(45).…”
Section: Rtn and Memory Variabilitymentioning
confidence: 99%
“…i) V n O m complexes cause leakage currents in p-n junctions [24][25][26]. Also besides VO, the V 2 O and V 3 O defects have been found to be effective recombination centers contributing in the reduction of the minority charge carriers lifetime induced by irradiation [3,27].…”
Section: Introductionmentioning
confidence: 99%